NFκB signaling in T cell memory - Daniels, Mark A.; Luera, Dezzarae; Teixeiro, Emma (Frontiers in Immunology, 2023)
Memory T cells play an essential role in protecting against infectious diseases and cancer and contribute to autoimmunity and transplant rejection. Understanding how they are generated and maintained in the context of infection or vaccination holds promise to improve current immune-based therapies. At the beginning of any immune response, naïve T cells are activated and differentiate into cells with effector function capabilities. In the context of infection, most of these cells die once the pathogenic antigen has been cleared. Only a few of them persist and differentiate into memory T cells. These memory T cells are essential to host immunity because they are long-lived and can perform effector functions immediately upon re-infection. How a cell becomes a memory T cell and continues being one for months and even years past the initial infection is still not fully understood. Recent reviews have thoroughly discussed the transcriptional, epigenomic, and metabolic mechanisms that govern T cell memory differentiation. Yet much less is known of how signaling pathways that are common circuitries of multiple environmental signals regulate T cell outcome and, precisely, T cell memory. The function of the NFκB signaling system is perhaps best understood in innate cells. Recent findings suggest that NFκB signaling plays an essential and unique role in generating and maintaining CD8 T cell memory. This review aims to summarize these findings and discuss the remaining questions in the field.